To rehabilitate or not to rehabilitate: that is the question for corrections! - MacKenzie, Doris L. (Criminology & public policy, 2018)
In this article, we review the recommendations on corrections made by the U.S. President's Commission on Law Enforcement and Administration of Justice under President Johnson in 1967 and compare these with the changes made in U.S. corrections over the past 50 years. Shortly after the Commission completed its report, dramatic changes occurred that impacted correctional policy and practice as support for law and order and correctional control moved corrections far from the Commission's recommendations for rehabilitation. The results of this research demonstrate that these approaches have not solved the nation's crime problems and have imposed hardships on individuals and communities. A current focus on evidence‐based corrections may provide a model for future decision making depending on whether the “times are ripe” for a return to a philosophy of rehabilitation. Any new commission will benefit from the research evidence that points to successful correctional interventions. Yet, there is much that still needs to be studied and learned. A new commission must be aware of and respond to the broader social conditions and beliefs and opinions of policy makers and the public that will influence receptivity to correctional reform. Recommendations should include clear guidelines for how research findings could be used to answer the still unanswered questions about rehabilitation interventions, as well as for how to ensure quality program delivery and public safety.